2007
DOI: 10.1080/13697130601037324
|View full text |Cite
|
Sign up to set email alerts
|

The perception of menopause and hormone therapy among women in Turkey

Abstract: Different perceptions of menopause among Turkish women are influenced by many factors, including cultural differences, level of education, regular exercise, social factors, and impact of the media. These need to be considered when studying the frequency and characteristics of menopausal problems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
2
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 26 publications
2
22
2
2
Order By: Relevance
“…It was also higher than the result reported by Ward et al in a survey among the general population in the UK (54%) [17] and that of Chim et al's survey in Singapore (51.7%) [24]. However, it was lower than the 82% of Uncu et al [22] and the 80% of Chedraui [20]. Our results indicate that arthralgia/myalgia is correlated with menopause status and becomes more severe as menopause progresses.…”
Section: Single Menopause Symptomcontrasting
confidence: 80%
See 1 more Smart Citation
“…It was also higher than the result reported by Ward et al in a survey among the general population in the UK (54%) [17] and that of Chim et al's survey in Singapore (51.7%) [24]. However, it was lower than the 82% of Uncu et al [22] and the 80% of Chedraui [20]. Our results indicate that arthralgia/myalgia is correlated with menopause status and becomes more severe as menopause progresses.…”
Section: Single Menopause Symptomcontrasting
confidence: 80%
“…Further investigation is needed to determine whether this is related to nurse working conditions. Arthralgia/myalgia, correlated with lack of exercise, high BMI, fluctuations in gonadal hormones [10], age, life style and general health [15], is one of the most severe symptoms of menopause syndrome [18,22,23]. In our survey it ranked third (69.55%).…”
Section: Single Menopause Symptommentioning
confidence: 88%
“…Our finding is in conformity with the studies performed on the same as well as the other cultural groups in terms of the effect of educational level on menopausal symptoms. [14,15] We know that menopause itself may cause weight gain and a shift in the distribution of fat. [16] Although some women in this study did not answer the question about BMI, among those who answered, only ¼ had normal BMI and the rest were either overweight or obese.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, studies on Asian women from different ethnic backgrounds have reported lower symptom prevalence rates between 10% and 50% [14]. The studies in Turkey showed a prevalence of 35%-90% [15-17]. The duration, severity and impact of these symptoms vary tremendously from person to person and population to population, but menopausal symptoms can profoundly affect personal and social functioning in affected individuals.…”
Section: Introductionmentioning
confidence: 99%